Implicações das categorizações profissionais e de cor da pele no preconceito - Feitoza, João Paulo Machado (2012)
Prejudice has occupied large space in discussions on field of interpersonal relations, being approached differently by many researchers in social psychology since the last century. Even today, much is discussed about what causes and how is the dynamics of this phenomenon. Although the various theoretical approaches and levels of analysis in social psychology have endeavored to uncover these problems, little has been done in the direction of recognizing the effect of this phenomenon in the relations between workers. The few studies identified in this area focus on the established race relations. Other new forms of prejudice arising from social categorization, not only racial, has recently been studied by these researchers, but there is still much to discover. In Brazil, in some public educational institutions, work place relations are subject of frequent conflicts informally observed by staff and, a few times, registered in reports recorded in complain sectors. This paper hypothesizes that some of these conflicts arise because of there is racial prejudice among workers in white and black skin color, in the other hand some prejudices comes from a professional bias, possibly derived from the social categorization of job functions. Therefore, considering the need to test this hypothesis, this study aimed to investigate the influence of the double and simultaneous professional and categorization of skin color in implicit and explicit prejudice directed at employees of a public university. We sought to compare whether the independent variables related to the functions and skin color would promote interaction of a way to recognize the extent of automatic prejudice and explicit prejudice. To achieve this goal, research was undertaken using the method of the Implicit Association Test, with classic and emotional setup, and also professional and racial prejudice scales. The data allowed us to verify evidence of the simultaneous influence of these variables on the expression of implicit prejudice. We observed similar results as study 1, in the literature on confirmation bias against blacks. But in study 2, there was only prejudice directed by Blacks to target employees with dark skin color, and in study 3 was obtained correlation between the measures used, implying the validation of the technique used. It follows that those who exercise the profession of employees and have dark skin color tend to be targets of prejudice.